Experimental study of wet porous sand layer air-drying characteristics. (February 2020) - Min, J.C.; Zhang, Y.; Tang, Y.C.
Abstract: An experimental study has been carried out to investigate the convective air-drying characteristics of a wet sand layer. The experimental setup allows dynamic measurements of both sand layer weight and temperature, with hot air flowing towards the sand layer surface to ensure a uniform drying of it. Experiments are conducted for a 4 mm thick sand layer for three air temperatures of 45, 60 and 75 °C. The lumped parameter method is used to analyze the sand layer heat transfer. The results show that the sand layer temperature continuously increases throughout the drying process, which can be divided into three stages, i.e. the initial rapid, intermediate slow, and final rapid increase stages. There is no constant temperature stage that is often observed in water film evaporation experiment. The drying process can also be divided into three stages according to the sand layer drying rate variation, they are the increasing, constant, and decreasing rate stages, which roughly correspond to the three temperature rise stages. The lumped parameter analysis result supports that the convective heat from the hot air is used mainly for the water evaporation.